2018
DOI: 10.1002/jsfa.8802
|View full text |Cite
|
Sign up to set email alerts
|

The Microvine, a plant model to study the effect of vine‐shoot extract on the accumulation of glycosylated aroma precursors in grapes

Abstract: Extrapolation of the results to grapevines suggests that vine-shoot extract treatment could modulate the synthesis of grape glycosylated aroma precursors. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Interestingly, in this process, aroma volatiles were absorbed and glycosylated in the plant, and then liberated during winemaking. In a recent research study, it was shown that an aqueous extract of toasted Airen ( V. vinifera) lignified canes sprayed onto microvine shoots increased total glycosylated aroma precursors by more than three times, from 126.27 to 434.05 µ L −1 . This demonstrates that it is possible to manipulate grape aroma composition by spraying different molecules onto the plant.…”
Section: Agronomic Practicesmentioning
confidence: 99%
“…Interestingly, in this process, aroma volatiles were absorbed and glycosylated in the plant, and then liberated during winemaking. In a recent research study, it was shown that an aqueous extract of toasted Airen ( V. vinifera) lignified canes sprayed onto microvine shoots increased total glycosylated aroma precursors by more than three times, from 126.27 to 434.05 µ L −1 . This demonstrates that it is possible to manipulate grape aroma composition by spraying different molecules onto the plant.…”
Section: Agronomic Practicesmentioning
confidence: 99%
“…In this study, we have measured at the same time the main berry traits that could vary with temperature increase in 33 V. vinifera genotypes. The whole genotype set consisted in a first subset of wine grape cultivars and a second subset of microvine offspring, this latter model being very promising for both physiological and genetic studies ( Chaib et al, 2010 ; Rienth et al, 2016b ; Luchaire et al, 2017 ; Sanchez-Gomez et al, 2017 ). The phenotypic diversity for growth and solutes accumulation was characterized at two critical stages of grapevine fruit development: (i) the end of green growth phase, when the berry stops loading organic acids and (ii) the end of ripening, when the contents of water and sugars reach their maximum.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 10 GSTs were up-regulated (6 in BR and 5 in MR), while two were down-regulated in BR. Genes generally annotated as CAT (3), POD (4), chaperone for SOD (1), and RX (19) were modulated by OW in the BR berry with some genes induced and others repressed.…”
Section: Antioxidant Homeostasismentioning
confidence: 99%
“…Carrying the Vvigai1 mutation, microvines exhibit a continuous owering, simultaneously displaying all the successive stages of fruit development on a single shoot 15 . This model has already facilitated transcriptomics approaches of the circadian cycle 16 , high-temperature stresses 17,18 , metabolomics works surveying glycosylated aroma precursors 19,20 , and several berry developmental studies [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%